Effects of cyanobacterial biomass on avian reproduction: a Japanese quail model - Damková, Veronika; Sedláčková, Jana; Banďouchová, Hana; Pecková, Lucie; Vitula, František; Hilscherová, Klára; Pašková, Veronika; Kohoutek, Jiří; Pohanka, Miroslav; Pikula, Jiří (Neuro-endocrinology letters, 2009)
OBJECTIVES: The present study was aimed at evaluation of the response of Japanese quails to cyanobacterial biomass administered in feed using biochemical profiles and parameters of reproduction. DESIGN: Effects of cyanobacterial biomass were studied according to the OECD 206 Guideline on Avian Reproduction Toxicity. A total of 16 control and 16 experimental pairs (32 males and 32 females) were analyzed. The chronic exposure of parent birds lasted eight weeks with the daily sum of 61.62 microg MCs including 26.54 microg MC-RR, 7.62 microg MC-YR and 27.39 microg MC-LR. RESULTS: There was no mortality both in control and cyanobacterial-biomass-exposed adults during the present study. Nor did the birds show any clinical signs of intoxication. Lactate dehydrogenase activity was increased about three-fold in exposed birds. No other biochemical parameters were showing significant differences. A total of 824 and 821 eggs were laid by control and exposed birds, respectively, during the eight-week study period. Eggs laid by cyanobacterial-biomass-exposed hens had lower weight than in controls (11.99+/-1.13g and 12.40+/-1.27g, respectively; p<0.01). Egg viability, hatchability, and the effect of hatching in control and experimental birds were 79.6+/-9.3 and 86.8+/-8.2% (p<0.05), 83.2+/-12.6 and 90.1+/-9.3%, and 65.2+/-17.7 and 77.7+/-15.2% (p<0.05), respectively. There was also a statistically significant difference in the number of 14-day old survivors per hen per day in control and experimental birds (0.38+/-0.02 and 0.43+/-0.01 %, respectively). CONCLUSION: The lower weight of eggs produced by exposed parental hens was not reflected in their biological quality. On the contrary, reproductive parameters in cyanobacterial-biomass-exposed birds were better than in the control group. It might be hypothesized that compounds of hormonal activity could be present in the complex cyanobacterial biomass. However, further research into this issue is necessary.
Keywords: Female; Animals; mužské pohlaví; L-laktátdehydrogenasa; Random Allocation; ovum; časové faktory; Reproduction; sinice; náhodné rozdělení; dieta; rozmnožování; zvířata; Ovum; Time Factors; Diet; ženské pohlaví; Cyanobacteria; L-Lactate Dehydrogenase; Male; Coturnix